Is aclidinium alone or combined with a LABA a rational choice for symptomatic COPD patients?. Issue 1 (December 2017) - Blasi, F.; Canonica, G.; Miravitlles, M.
Abstract Background As emphasized by international recommendations and largely confirmed by clinical experience, long-acting bronchodilators play a central role in the maintenance treatment of chronic obstructive pulmonary disease (COPD) due to their proven efficacy in reducing airflow obstruction and improving symptoms. Main body There are some important aspects to define with regard to inhalation therapy for COPD, particularly those concerning the selection criteria and the optimal use of long-acting bronchodilators. First of all, it needs to be determined in which patients and clinical situations monotherapy with one bronchodilator, such as a long-acting muscarinic antagonist (LAMA), should be considered adequate, and in which cases the use of combination therapies, such as the "double bronchodilation" with a LAMA and a long-acting β2-agonist (LABA), should be preferred. Another critical issue concerns the effect of the frequency of daily administration of inhaled agents on the control of symptoms during the 24 h. COPD symptoms are known to exhibit considerable circadian variability with worsening in the early morning, and a significant proportion of patients have disease-related sleep disorders which can adversely affect their quality of life. The worsening of symptoms in the early morning may be due, at least in part, to a reduction in airway caliber caused by an increased "cholinergic tone" at night. As such, the coverage of nighttime and early morning symptoms is a reasonable therapeutic goal, which can be achieved by many patients using LAMAs such as aclidinium bromide twice daily (BID). Therapeutic adherence is known to be a multifactorial phenomenon that is frequently affected by other aspects than dosing frequency, including the technical features and ease of use of the inhalers. To this end, it should be mentioned that certain new-generation inhalers such as Genuair® have been associated in clinical trials with higher patient preference. Conclusion In this work, in addition to presenting an overview of the main evidence on the efficacy of COPD treatment with the LAMA aclidinium bromide BID, we suggest some selection criteria for the monotherapy with one long-acting bronchodilator or the combination therapy with LAMA and LABA in COPD patients, with particular reference to specific clinical scenarios.